Behcet’s disease: a review - Reyes-Weaver, Daniela Ann; Plata-Jimenez, Kevin Luis; Melo-Acevedo, Raul (International Journal of Research in Medical Sciences, 2021)
Behcet’s disease (BD) is a complex systemic vasculitis with an etiopathogenesis that remains unclear. It has a strong geographic association as well as a genetic propensity linked to the HLA-B51 factor and interactions between genetic and environmental factors. The typical age of onset is 25 to 40 years old and it is more common in men, who also have a more severe condition. Occlusive vasculitis is the hallmark of this condition, which can affect vessels of all diameters. Oral ulcers, genital ulcers, skin lesions, pathergy reaction as well as involvement of other systems and organs such as ophthalmic, neurological and vascular lesions, among others, are used to make the diagnosis. Uncontrolled neutrophil activation, activation of the humoral and cell immune systems, toxic proteins and infectious agents such as herpes simplex and streptococci are all involved in their pathophysiology. Due to the heterogeneity and several systems affected, the treatment is individualized and focused on treating each clinical manifestation.